Pengenalan Metode Pembiasaan Guru Pendidikan Agama Islam : Di SMA Negeri 2 Tembilahan - Moh Sain (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
Education is an integral part of human life. Education is a need, a social function, enlightenment, guidance, a means of growth that prepares and opens and forms the discipline of life. Therefore, the highs and lows of the life of a community of human activities are largely determined by their education. In the Unitary State of the Republic of Indonesia, where in fact the majority of the people embrace Islam, ideally Islamic Religious Education, underlies other educations, and becomes the prima donna for society, parents, and students, so that Islamic religious education also gets proportional time, not only in madrasas or schools with Islamic nuances, but also in public schools. The purpose of Islamic Religious Education is to assist in the formation of noble character, preparation for the life of the hereafter, growing the Islamic spirit, preparing students from a professional perspective, preparing to seek sustenance. So, one of the methods that can be applied in order to realize Islamic religious education in schools, especially public schools, is the habituation method. This habituation method is based on experience. The method has a very significant position to achieve the goal. Even the method as an art in transferring knowledge/subject matter to students is considered more significant than the material itself.